MODELS OF TECHNOLOGICAL INNOVATION - Inche Mitma, Jorge Luis (1998)
In this assay, highlights the importance of any strategy for proper management of technological innovation processes. The body of knowledge consists of a set of models involved in the creation and growth of enterprises, so that a model can be used to define, plan and implement economic development strategies.